Transdisciplinary Obesity Prevention Research Sciences (TOPRS) Curriculum Increases Knowledge About Complex Causes and Consequences of Obesity for Undergraduate Students - Barbara H. Fiese; Amber Hammons; Brenda Koester; Gabriela L. Garcia; Loran Parker; Dorothy Teegarden (Frontiers in Public Health, 2019)
Most researchers and public health officials would agree that the causes and consequences of obesity are complex and multi-faceted. However, curricula designed to address these complexities are limited and often guided by a single discipline. The purpose of the Transdisciplinary Obesity Prevention Research Sciences (TOPRS) program was to develop a “flip-the-classroom” curriculum on obesity prevention across multiple disciplines such that students would gain an appreciation of the complex origins of obesity. The curriculum is based on the 6 C's model (cell, child, clan, community, country, culture) that proposes a cell-to-society approach to obesity. Twenty video micro-lectures were developed and students were tested on content knowledge pre- and post-viewing. The curriculum was administered at three university sites to 74 undergraduate students across 23 declared majors from 2014–2016. There were significant gains in knowledge about the causes and consequences of obesity. Recommendations are offered to adopt this curriculum in undergraduate and other educational settings.